2016
DOI: 10.1590/1983-084x/15_187
|View full text |Cite
|
Sign up to set email alerts
|

Farinha da casca do fruto de Passiflora edulis f. flavicarpa Deg (maracujá-amarelo): do potencial terapêutico aos efeitos adversos

Abstract: RESUMO:O maracujá-amarelo (Passiflora edulis f. flavicarpa Deg) é considerado um alimento funcional, visto que, além de funções nutricionais, desempenha ações em vias metabólicas específicas. A farinha da casca do maracujá-amarelo (Passiflora edulis f. flavicarpa Deg) é rica em pectina. Esta fibra reduz a absorção de glicídios e lipídios, influenciando no metabolismo destes nutrientes. Portadores de patologias associadas às alterações no metabolismo glicêmico e lipidêmico têm utilizado este recurso de forma in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
(33 reference statements)
0
7
0
4
Order By: Relevance
“…Another conclusion of the Post et al [9] study about dietary fiber showed that, overall, an intervention involving fiber supplementation for type 2 diabetes mellitus could reduce fasting blood glucose and HbA1c, suggesting that increasing dietary fiber in the diet of patients with type 2 diabetes is beneficial and should be encouraged as a disease management strategy. According to Coqueiro et al [10] found similar results showing efficacy in the supplementation with the flour of the yellow Pfp, referring to the hypoglycemic and hypolipidemic action. The results found by Lima et al [11] showed that Pfp flour has an inhibitory effect on the absorption of sucrose in normal rats and a hypoglycemic effect in alloxan-induced diabetic rats.…”
mentioning
confidence: 84%
“…Another conclusion of the Post et al [9] study about dietary fiber showed that, overall, an intervention involving fiber supplementation for type 2 diabetes mellitus could reduce fasting blood glucose and HbA1c, suggesting that increasing dietary fiber in the diet of patients with type 2 diabetes is beneficial and should be encouraged as a disease management strategy. According to Coqueiro et al [10] found similar results showing efficacy in the supplementation with the flour of the yellow Pfp, referring to the hypoglycemic and hypolipidemic action. The results found by Lima et al [11] showed that Pfp flour has an inhibitory effect on the absorption of sucrose in normal rats and a hypoglycemic effect in alloxan-induced diabetic rats.…”
mentioning
confidence: 84%
“…Por otra parte, esta cáscara también puede ser usada para la obtención de harina por medio de la trituración (Angulo et al, 2018;Meza y Zambrano, 2018), de donde según Quezada (2013), realizó un estudio de deshidratación de este epicarpio para obtener harina, esta harina; luego fue adicionada a una granola, obteniendo como resultado un producto de buena calidad en comparación con la granola de trigo tradicional. Mientras tanto, Coqueiro et al (2016), sustentó la importancia de conocer los efectos adversos a la hora de producir harina del epicarpio; principalmente sobre el hecho de que esta fruta se encuentra expuesta a factores ambientales externos como son los plaguicidas.…”
Section: Epicarpiounclassified
“…The passionfruit peel (Passiflora edulis) is rich in soluble fibers, such as pectin, important in controlling blood levels of glucose and lipids [16]. It may aid in preventing gastrointestinal diseases, diabetes and obesity [17]. The reduction of sodium intake is a priority issue in the fight against chronic non-communicable diseases in the country, due to its relationship with the risk of hypertension, cardiovascular and renal diseases, among others [18].…”
Section: Introductionmentioning
confidence: 99%